2008
DOI: 10.1051/0004-6361:200809817
|View full text |Cite
|
Sign up to set email alerts
|

Early-type galaxies with core collapse supernovae

Abstract: Aims. It is widely accepted that the progenitors of core collapse SNe are young massive stars and therefore their host galaxies are mostly spiral or irregular galaxies dominated by a young stellar population. Surprisingly, among morphologically classified hosts of core collapse SNe, we find 22 cases where the host has been classified as an Elliptical or S0 galaxy. Methods. To clarify this apparent contradiction, we carry out a detailed morphological study and an extensive literature search for additional infor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 79 publications
(107 reference statements)
5
52
0
Order By: Relevance
“…Such a location of SN is in good agreement with the known correlations of core-collapse (Types Ibc and II) SNe with star formation in galaxies (e.g. James & Anderson 2006;Hakobyan et al 2008), including also star formation induced by an interaction with neighbor galaxies (e.g. Nazaryan et al 2013;Hakobyan et al 2014).…”
Section: Description Of the Systemsupporting
confidence: 88%
“…Such a location of SN is in good agreement with the known correlations of core-collapse (Types Ibc and II) SNe with star formation in galaxies (e.g. James & Anderson 2006;Hakobyan et al 2008), including also star formation induced by an interaction with neighbor galaxies (e.g. Nazaryan et al 2013;Hakobyan et al 2014).…”
Section: Description Of the Systemsupporting
confidence: 88%
“…According to the nearby SN rates estimated by Maoz et al (2011), a young star burst (<420 Myr) produces ten times more CC SNe than SNe Ia. Although a few CC SNe have been observed in elliptical galaxies that show signs of star formation from UV observations (e.g., Hakobyan et al 2008;Suh et al 2011), they are much rarer than SNe Ia. Therefore, at least part of SNe Ia probably come from old SPs, as demonstrated by Maoz et al (2011.…”
Section: Correlation To Star-forming Regionsmentioning
confidence: 92%
“…Figure 15 presents the cases of CC SNe in early-type hosts. Hakobyan et al (2008) already reported and investigated in detail two cases of such CC SNe in early-type galaxies (2000ds (Filippenko & Chornock 2000) has been confirmed to be an S0, with a central region showing dust and a disky central gas distribution (e.g., Hakobyan et al 2008). According to the outer isophotal structure and radial surface brightness profile of the host of SN 2006ee (Puckett et al 2006), this must be an S0 galaxy.…”
Section: Distribution Of Sn Typesmentioning
confidence: 93%
“…They suggested that to understand the dependence of SN type on the host galaxy population, it is more important to obtain accurate morphological classifications than it is to increase the size of the sample. For example, among ∼800 morphologically classified hosts of CC SNe, Hakobyan et al (2008) found 22 cases where the host had been classified as E or S0. Following a detailed morphological analysis, they found that among these 22 early-type objects, 17 are in fact misclassified spiral galaxies, one is a misclassified irregular, and one is a misclassified ring galaxy, leaving only 3 early-type galaxies 15 .…”
Section: Comparison Of Host Galaxy Morphological Classificationsmentioning
confidence: 99%